Implementasi Model Pembelajaran Argumentasi Dialogis dalam Pembelajaran Fisika untuk Meningkatkan Kemampuan Argumentasi Ilmiah Siswa SMA - Muslim Muslim (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2015)
Abstract Low ability of scientific arguments related to the students' learning process in the physics classroom that has not habituate scientific argumentation ability. This study aimed to examine the effect of the implementation of arguments dialogical learning model to increase students' ability of scientific argumentation. Argumentation dialogical learning model consists of five phases of learning, namely stages: (1) identification of the problem; (2) group argument discussion; (3) classroom argument discussion; (4) class mediation; and (5) the integration of knowledge. Each stage involves students learning activities directly in order to develop the ability of scientific argumentation. The pre-experimental method with the one group pretest and posttest design used in this research. The essay ability of the scientific arguments test and observation sheet used as a research instruments. Subjects in this study were students of 10th grade in one of the state senior high schools in Bandung, which is determined by random cluster sampling technique. The results show there is an increase in the ability of the student to the acquisition of scientific arguments with medium category after argument dialogical learning model implemented and it was concluded that the implementation of arguments dialogical learning model increased the students’ ability of scientific argumentation. Keywords: argument dialogic learning model, scientific argumentation ability Abstrak Rendahnya kemampuan argumentasi ilmiah siswa terkait proses pembelajaran fisika di kelas yang belum melatihkan kemampuan argumentasi ilmiah. Penelitian ini bertujuan melihat pengaruh implementasi model pembelajaran argumentasi dialogis terhadap kemampuan argumentasi ilmiah siswa. Model pembelajaran argumentasi dialogis terdiri dari lima tahap pembelajaran, yaitu: (1) identifikasi masalah; (2) diskusi argumentasi kelompok; (3) diskusi argumentasi kelas; (4) mediasi kelas; dan (5) integrasi pengetahuan. Setiap tahapan melibatkan secara langsung aktivitas siswa untuk berlatih mengembangkan kemampuan argumentasi ilmiah. Metode penelitian yang digunakan adalah pre-experiment dengan desain penelitian one group pretest and posttest. Instrumen penelitian yang digunakan meliputi tes kemampuan argumentasi ilmiah berbentuk uraian dan lembar observasi. Subyek dalam penelitian ini adalah siswa kelas X pada salah satu SMA Negeri di Kota Bandung yang ditentukan dengan teknik cluster random sampling. Hasil penelitian menunjukkan peningkatan kemampuan argumentasi ilmiah siswa dengan kategori sedang setelah diimplementasikan model pembelajaran argumentasi dialogis, sehingga dapat disimpulkan bahwa implementasi model pembelajaran argumentasi dialogis berpengaruh terhadap kemampuan argumentasi ilmiah siswa. Kata-kata kunci: model pembelajaran argumentasi dialogis, kemampuan argumentasi ilmiah